Foreign Firm Characteristics, Absorptive Capacity and the Institutional Framework - Farole, Thomas; Winkler, Deborah (World Bank, Washingon, DC, 2013)
Using a cross-section of more than 25,000 domestic manufacturing firms in 78 low and middle-income countries from the World Bank's Enterprise Surveys, this paper assesses how mediating factors influence intra-industry productivity spillovers to domestic firms from foreign direct investment. It identifies three types of mediating factors: (i) foreign direct investment spillover potential, (ii) domestic firm absorptive capacity, and (iii) the host country's institutional framework. It finds that all three affect the extent and direction of foreign direct investment spillovers on domestic firm productivity. However, the impact of mediating factors depends significantly on the level of domestic firms' productivity and the structure of foreign ownership.